Cross-Cultural Adaptation and Psychometric Properties of Moral Injury Symptoms Scale - Zasiekina, Larysa; Kozihora, Mariia (Psychological Prospects Journal, 2022)
Purpose. The study aims to translate, culturally adopt and explore psychometric properties of Moral Injury Symptoms Scale – Military Version – Short Form (MISS-M-SF) in civilian population during war. Evidence consistently suggests, that moral injury was common among veterans and active duty military with PTSD symptoms. However, recent findings show that moral injury could occur in civilian population and professional staff, who are at high risk situations.Methods. Teachers and students of Lutsk pedagogical college and teachers (n=111) from the program “State Support of Teachers during the War” were recruited via State Education Quality Assurance Service and participated in the study during 26 April-15 May 2022, mean age is 21,93±8.58, representatives of Volyn, Lviv and Rivne oblasts. The study applies the guidelines of WHO for translation and cultural adaptation of psychodiagnostic instruments and follows four stages, namely direct translation (3 translators, who are familiar with psychological terminology), group of experts for back translation (2 translators), pre-testing and cognitive interview, and the final version.Results. Reliability was assessed through the internal consistency using Cronbach’s α= .70 (n = 111), and the test–retest reliability in 8 days, r=.67, p≤.01 (n=32). The study assesses discriminant validity of MISS-M-SF through association with PCL-5, which is r=.04 and MISS-M-SF through association with GAD-7, which is r=.07, p≥.05. Convergent validity is expressed by the correlation of MISS-M-SF and other measures of emotional distress, namely PQH (r=.28 p≤.05). Construct validity is in the range of 0,45-0,71.  Descriptive statistics were performed to describe average and median scores, standard deviations (SD), and ranges on the MISS-M-SF and its individual items for which IBM SPSS Statistics, version 22, was used.Conclusions. The obtained results indicate the cultural appropriateness and psychometric properties of MISS-M-SF, which allow to assess moral injury in civilian population during war.
Keywords: moral traumatization, civilian population, traumatic experience, post-traumatic stress disorder.